Schooling health: the critical contribution of curriculum in the 1980s. Issue 2 (2nd October 2017) - Leahy, Deana; Penney, Dawn; Welch, Rosie
Abstract : Purpose: Public health authorities have long regarded schools as important sites for improving children and young people's health. In Australia, and elsewhere, lessons on health have been an integral component of public health's strategy mix. Historical accounts of schools' involvement in public health lack discussion of the role of health education curriculum. The purpose of this paper is to redress this silence and illustrate the ways health education functioned as a key governmental apparatus in Victoria in the 1980s. Design/methodology/approach: The paper draws on governmentality studies to consider the explicit governmental role of official health education curriculum in the 1980s in Victoria, Australia. The authors conduct a discourse analysis of the three official curriculum texts that were released during this period to consider the main governmental rationalities and techniques that were assembled together by curriculum writers. Findings: School health education functions as a key governmental apparatus of governmentality. One of its major functions is to provide opportunities to responsibilise young people with an aim to ensure that that they can perform their duty to be well. The authors demonstrate the central role of policy events in the 1970s and how they contributed to conditions of possibility that shaped versions of health education throughout the 1980s and beyond. Despite challenges posed by the critical turn in health education in the late 1980s, the governmental forces that shape health education are strong and have remained difficult to displace. Originality/value: Many public health and schooling histories fail to take into account insights from the history of education and curriculum studies. The authors argue that in order to grasp the complexities of school health education, we need to consider insights afforded by curriculum histories. Historical insights can provide us with an understanding of the changing approaches to governing health in schools.